Ash Deposition Characteristics of Industrial Biomass Waste and Agricultural Residues. (2019) - Yub Harun, Noorfidza; Jin Han, Tang; Vijayakumar, Tharunan; Saeed, Anwar; Afzal, MT
Abstract: Resolution of industrial waste as thermal source is an effective way to transform the unwanted scheduled waste into renewable energy. Plant residues also contributed to enhance its utilization and considered a reliable resource for energy uses. Both sectors of feedstock are aimed to produce significant amount of thermal energy through combustion. Ash deposition behaviors of biomass fuel from industrial sludge and agricultural waste have been analyzed. Sludge and effluent were carefully taken from petroleum crude processing plant (PGB) and palm oil mill (POME), respectively. Rice husk and kenaf were obtained from local neighborhoods farm. The effective utilization of potential biofuel is evaluated based on its ash content, chemical composition and its ash slagging and fouling tendency. PGB and POME were evaluated to have energy content about 21.35 MJ/kg and 15.238 MJ/kg respectively. While kenaf and rice husk each has 16.14 MJ/kg and 15.19 MJ/kg, respectively. Ash content of PGB sludge was around 30.0% where POME sludge was about 38.0%. Kenaf showed a better biomass type as the ash content was only 2% ash, whereas rice husk ash content was 11%. To illustrate the realistic combustion condition under different temperature, the effect of ashing temperatures that are 525°C, 575°C and 625°C to the ash deposition characteristics is also examined. This variation of ashing temperature will also deflect the chemical composition especially the heavy metal element in the sludge ash. Furthermore, the physical ash deposition and deformation characteristics are observed by ash fusion test. Conclusively, PGB, POME, rice husk and kenaf biomass are feasible to produce sufficient thermal energy as well as stable at high temperature with their distinct chemical composition, but their individual range ashing temperature may deficient the thermal process differently.